2021
DOI: 10.1016/j.neubiorev.2020.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Visual mental imagery engages the left fusiform gyrus, but not the early visual cortex: A meta-analysis of neuroimaging evidence

Abstract: The dominant neural model of visual mental imagery (VMI) stipulates that memories from the medial temporal lobe acquire sensory features in early visual areas. However, neurological patients with damage restricted to the occipital cortex typically show perfectly vivid VMI, while more anterior damages extending into the temporal lobe, especially in the left hemisphere, often cause VMI impairments. Here we present two major results reconciling neuroimaging findings in neurotypical subjects with the performance o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 143 publications
(172 reference statements)
9
107
1
Order By: Relevance
“…The left fusiform lesion is highly consistent with the evidence reviewed above, and further specifies the crucial lesion location within the extensive left temporal damage occurring in most patients with visual mental imagery deficits (Bartolomeo 2002(Bartolomeo , 2008. Starting from the seminal case of visual agnosia described by Lissauer (see Bartolomeo 2021), patients with more posterior lesions in the left occipital lobe can instead exhibit well preserved abilities of visual mental imagery (Bartolomeo 2002).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The left fusiform lesion is highly consistent with the evidence reviewed above, and further specifies the crucial lesion location within the extensive left temporal damage occurring in most patients with visual mental imagery deficits (Bartolomeo 2002(Bartolomeo , 2008. Starting from the seminal case of visual agnosia described by Lissauer (see Bartolomeo 2021), patients with more posterior lesions in the left occipital lobe can instead exhibit well preserved abilities of visual mental imagery (Bartolomeo 2002).…”
supporting
confidence: 73%
“…Results from the past twenty years of functional magnetic resonance imaging (fMRI) studies on endogenous visual mental imagery in healthy individuals have been recently summarized in a meta-analysis (Spagna et al 2021). A re-examination of the patterns of hemispheric laterality observed in the fMRI literature combined with positron emission tomography studies shows evidence that is consistent with the neuropsychological evidence described above.…”
Section: Evidence From Neuroimagingmentioning
confidence: 73%
“…For instance, the left OFC was dominant during conscious assessment of the emotional quality of an odor ( Royet et al, 2003 ). In terms of left fusiform activation, Spagna et al (2021) reported that robust activity in the left fusiform gyrus was associated with visual mental imagery. Evidence from patients with brain damage indicates that visual mental imagery is impaired after extensive damage of the temporal lobe, especially that in the left hemisphere ( Bartolomeo, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, greater lower and upper alpha values were detected at the temporal site of the right hemisphere. Spagna and coworkers (Spagna et al, 2021) discovered that visual mental imagery engages the left fusiform gyrus, and patients with extensive left temporal damage often have this type of imagery impairment. But speech imagery blocks the alpha and theta band in the left hemispheric frontal and temporal regions (Chengaiyan et al, 2018).…”
Section: Mental and Motor Imagery In Neurosciencementioning
confidence: 99%